(untitled) (Quarterly Journal of Econometrics Research, 2017)
The rationale of this study was to examine empirically how components of public sector size relates to GDP growth in East Africa from 1985-2015. Using balanced panel fixed or random effect model, public sector expenditure was disaggregated to scrutinize its effect of growth. The research tested for panel unit root and found that only two variables, that is, real GDP growth and capital spending - are stationary at level. The finding confirms the conventional view that relative capital spending - advances economic growth while consumption expenditure retards it. Finally, human capital allocation was insignificant. This study suggests that for these countries, the policy of increasing public sector size on investment budget to promote GDP growth will be appropriate, but fewer funds should be directed towards other governmental programs.